Early Transcriptional Response to Monensin in Sensitive and Resistant Strains of Eimeria tenella - Zhang, Hongtao; Zhang, Lei; Si, Hongbin; Liu, Xianyong; Suo, Xun; Hu, Dandan (Frontiers in Microbiology, 2022)
Eimeria parasites are the causative agents of coccidiosis, a common parasitic disease in poultry and livestock that causes significant economic losses to the animal husbandry industry. Ionophore coccidiostats, such as monensin and salinomycin, are widely used for prophylaxis of coccidiosis in poultry. Unfortunately, widespread drug resistance has compromised their efficacy. As a result, there is an increasing need to understand targets and resistance mechanisms to anticoccidials. However, how Eimeria parasite genes respond to ionophores remains unclear. In this study, resistance to monensin was induced in E. tenella through serial generations of selection. Both sensitive and resistant E. tenella sporozoites were treated with 5 μg/mL monensin for 0 h, 2 h and 4 h, respectively. Gene transcription profiles were then compared by high-throughput sequencing. The results showed that protein translation-related genes were significantly down-regulated after drug induction. A total of 1848 DEGs were detected in the sensitive strain after 2 h of exposure, while only 31 were detected in the resistant strain. Among these DEGs in the sensitive strain, genes associated with protein degradation were significantly up-regulated, supporting the autophagy-like parasite killing theory. Four hours of exposure resulted in additional 626 and 621 DEGs for sensitive and resistant strains, respectively. This result implies that the gene transcription in sensitive strain is more susceptible to monensin treatment. Our results provide gene expression landscapes of E. tenella following monensin treatment. These data will contribute to a better understanding of the mechanism of drug resistance to polyether ionophores in coccidia.